Determination of spatial distribution of cardiovascular disease risk factors at the Dikgale, Mamabolo, Mothiba Health and Demographic Surveillance Site, Limpopo Province, South Africa - Makgobatlou, Maite Dineo (My University, 2024)
Determination of spatial distribution of cardiovascular disease risk factors at the Dikgale, Mamabolo, Mothiba health and demographic surveillance site, Limpopo province, South Africa. *Makgobatlou MD, *Choma SSR, *Satekge T Department of Pathology, University of Limpopo Background: For proper management and control of diseases, epidemiological studies focused on the spatial distribution of communicable diseases. Little attention has been given to non-communicable diseases, especially amongst the black population. Aim: To determine the spatial distribution of cardiovascular disease risk factors (hypertension, obesity, dyslipidaemia, diabetes mellitus, alcohol consumption, smoking) among adults residing in the Dikgale, Mamabolo, Mothapo health and demographic surveillance site (DIMAMO HDSS), Limpopo province, South Africa. Methodology: This was a retrospective, descriptive, cross-sectional and quantitative research. The study used data collected from the Africa Wits-INDEPTH Partnership for Genomic Research (AWI-Gen) phase 1. A total sample size of 791 (women-549 and men-242) was used. Data extraction tool was used to obtain variables such as demographic status, socio-economic status, lifestyle, substance use, laboratory measurements, Geographic Information System (GIS) coordinates as well as the general health of the participants. The data were analysed using Statistical Package for Social Sciences (SPSS) software for statistical analysis and the local Moran I statistic for the spatial analysis. Results: Most of the biomedical risk factors were more common among women compared to men, hypertension (51.7% vs 37.6%), obesity (49.5% vs 3.3%), dyslipidaemia (22.6% vs 15.0%) and diabetes mellitus (7.4% vs 4.6%). In contrast, most of the behavioural risk factors were more common among men compared to women, alcohol consumption (57.4% vs 13.8%) and smoking (82.6% vs 7.5%). Metabolic syndrome was more common in women (15.7%) compared to men (2.1%). In the total population, the proportions of metabolic syndrome and high Framingham score were 11.5% and 9.9% respectively. Binary and multivariate regression analysis showed that diabetes and central obesity may have contributed to hypertension, high waist circumference may have contributed to the distribution of diabetes mellitus, obesity was found to be a determinant for the distribution of dyslipidaemia and there was no association between both alcohol consumption and smoking with social determinants. Conclusion: Biomedical cardiovascular disease risk factors were more common among women and in clusters A and B whilst behavioural cardiovascular risk factors were more common among men and in cluster D. Most of the cardiovascular disease risk factors were more common in village clusters A and B. The reason for this may be attributed to age, gender and behavioural risk factors.
Thesis (M.Sc. (Medical Sciences)) -- University of Limpopo, 2024
Keywords: Cariiovascular risk factors; Hypertension; Diabetes mellitus; Obesity; Dyslipidamia; Alcohol consumption; Smoking; Spartial distribution; Cardiovascular disease diagnostic equipment industry; Cardiovascular system -- Diseases -- Nursing; Cardiovascular system -- Diseases